ANU Productions The Monto Cycle - Singleton, Brian; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2016)
This book sets out strategies of analysis of the award-winning tetralogy of performances (2010-14) by ANU Productions known as 'The Monto Cycle'. Set within a quarter square mile of Dublin's north inner city, colloquially known as The Monto, these performances featured social concerns that have blighted the area over the past 100 years, including prostitution, trafficking, asylum-seeking, heroin addiction, and the scandal of the Magdalene laundries. While placing the four productions in their social, historical, cultural and economic contexts, the book examines these performances that operated at the intersection of performance, installation, visual art, choreography, site-responsive and community arts. In doing so, it explores their concerns with time, place, history, memory, the city, 'affect', and the self as agent of action. Brian Singleton is Samuel Beckett Professor Drama & Theatre, and Academic Director of The Lir - National Academy of Dramatic Art at Trinity College Dublin, Ireland. He is the author of Masculinities and the Contemporary Irish Theatre (2011, 2015), and edits (with Elaine Aston) the book series 'Contemporary Performance InterActions' for Palgrave Macmillan.
1. Introduction -- 2. World's End Lane -- 3. Laundry -- 4. The Boys of Foley Street -- 5. Vardo -- 6. Conclusion -- Bibliography.
Keywords: Performing arts; Theater-History.; Social history; Ethnology-Europe.; British Culture; History of Britain and Ireland